Remembering, Second Edition : A Phenomenological Study - Casey, Edward S., 1939- (Book collections on Project MUSE., 2000)
RememberingA Phenomenological StudySecond EditionEdward S. CaseyA pioneering investigation of the multiple ways of remembering and the difference that memory makes in our daily lives. A Choice Outstanding Academic Book""An excellent book that provides an in-depth phenomenological and philosophical study of memory.""--Choice"" ... a stunning revelation of the pervasiveness of memory in our lives.""--Contemporary Psychology""[Remembering] presents a study of remembering that is fondly attentive to its rich diversity, its intricacy of structure and detail, and its wide-ranging efficacy in our every